Pengaruh Dukungan Keluarga Terhadap Pencegahan Kekambuhan Pasien Skizofrenia yang Berobat Jalan di RSKD Duren Sawit Jakarta Timur - Viktorianus Viktorianus; Elwindra Elwindra (STIKes Persada Husada Indonesia, 2017)
Schizophrenia is one form of mental disorder still considered as an embarrassing disease, a disgrace for the patients and their families. Until now, the handling of schizophrenia patients both at home and in the hospital is still unsatisfactory. Family support for people with schizophrenia becomes a very important aspect in the process of relapse prevention in addition to drugs and psychological therapy provided by a doctor. The purpose of this study is to determine the effect of family supports (emotional, esteem, instrumental and informative) on the prevention of relapse of schizophrenia outpatients at RSKD Duren Sawit East Jakarta. This study was conducted in July 2016. The study population was the families of 150 schizophrenia outpatients of RSKD Duren Sawit East Jakarta. Samples were from 60 respondents and sampling done by Accidental Sampling. Results of the study found no significant association between patients’ characteristics (age, gender, education, occupation and marital status) and relapse prevention. Overall results showed family support has a significant effect on the prevention of relapse of schizophrenia outpatients at RSKD Duren Sawit East Jakarta. The better the family support will result in better the recurrence prevention of the patient.